KARAKTERISTIK IBU YANG MELAHIRKAN BAYI DENGAN KELAINAN KONGENITAL DI RSUD DR. PIRNGADI MEDAN TAHUN 2007-2011 - stella mariska; Sori Muda Sarumpaet; Jemadi . (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2012)
Congenital anomaly is a disorder that has been around since birth can be caused by genetic or non-genetic factors. In Indonesia infant mortality  is mainly due to congenital anomalies 7%. To know the characteristics of mother who gave birth a baby with a congenital anomaly in Dr. Pirngadi Hospital Medan in 2007-2011 is used descriptive research with case series design. Population was 102 mothers who gave birth a baby with a congenital anomalies. The data had done analyzed by using Chi-square, Mann-Whitney, and Kruskal-wallis test. The highest proportion of maternal characteristics: age 20-35 years old 84.3 %, Javanese 45,0%, senior high school education 48,8%, housewife 78,3%, live in Medan 54,9%, gestational age 37 – 40 weeks 65,3%, and no pregnancy complications history 66,7%. The proportion of babies with congenital anomalies, the highest type of congenital anomalies in the gastro-intestinal system 66,7%, male 54,9%, non-surgical 51,0%, average length of stay 7,57 days (8 days), outpatient control 46,1%. There was a difference between proportion of maternal age and the type of congenital anomalies (p = 0.012). There is no difference between the proportion of type of congenital anomalies and medical act (p = 1.000). There is no difference between the average length of stay and the type of congenital anomalies (p = 0,126). There is a difference between average length of stay and the condition when go home (p = 0.0001). The hospital is expected to to improve services and management, complete records especially the maternal medical-obstetrict  history. Key words : Baby with Congenital Anomaly, Characteristics of Mother